Changing the subject of an equation involves solving for another variable in the equation
The equation of t is [tex]t=\frac{\sqrt{y_i-y_o}}{N}[/tex]
The equation is given as:
[tex]N=\sqrt[2]{\frac{y_i-y_o}{t^2}}[/tex]
Rewrite the equation as:
[tex]N=\sqrt{\frac{y_i-y_o}{t^2}}[/tex]
Evaluate the square root of t^2
[tex]N=\frac{\sqrt{y_i-y_o}}{t}[/tex]
Multiply both sides by t
[tex]Nt=\sqrt{y_i-y_o}[/tex]
Make t the subject, in the above equation
[tex]t=\frac{\sqrt{y_i-y_o}}{N}[/tex]
Hence, the equation of t is [tex]t=\frac{\sqrt{y_i-y_o}}{N}[/tex]
Read more about subject of formula at:
https://brainly.com/question/657646